Syphilis and some other STIs in the Russian Federation: past, present and ways to control of the epidemiological situation in the future - Tatiana V. Krasnoselskikh; Evgeny V. Sokolovskiy; Margarita R. Rakhmatulina; Elena Yu. Novoselova; Lidia E. Melekhina (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
The article is devoted to assessing the situation with syphilis and other sexually transmitted infections in the USSR and Russia in the period after the Second World War. On the basis of long-term statistical data, the patterns of rises and decreases in syphilis, gonorrhea, chlamydia infection are analyzed, possible factors influencing the epidemic process are discussed and a comparative assessment of the current situation in Russia and Western countries is carried out. Comparing to the previous year, there was an increase of the syphilis incidence by 39.4% in 2021, by 33.7% in 2022 and by 14.7% in the first 4 months of 2023. The incidence of gonococcal infection increased by 10.4%, 10.0% and 5.5%, respectively. The attention is drawn to the negative trend of an increase of latent and late syphilis among other forms, as well as rising number of late neurosyphilis and late cardiovascular syphilis cases. In view of the predicted increase in the incidence of syphilis and other STIs in the coming years, the authors emphasize the urgent need to develop and implement a state interdisciplinary program aimed to epidemiological monitoring, improvement of the diagnosis and treatment, prevention of the dissemination of syphilis and other STIs and controlling of factors that negatively affect the reproductive health of the nation.